Pengembangan Model Optimasi Konsumsi Bahan Bakar PLTU terhadap Produksi Energi Listrik pada Sistem Jawa-Bali - Muhammad Alif Ihsan; Zara Safira Ramadhani; Wan Habibi Rahman Barus; Nadiya Maharani (Tekinfo: Jurnal Ilmiah Teknik Industri dan Informasi, 2026)
The current state of Indonesia's power system still predominantly uses coal as fuel. On the other hand, there are demands for cost efficiency and emission reduction. The Java-Bali system, which is a national burden, faces the need for more efficient management of coal-fired power plants, especially when the available capacity must meet existing demand. An approach that can be applied is the allocation of production between PLTU operators based on coal consumption efficiency without adding coal capacity. This study aims to minimize coal consumption at the Java-Bali PLTU by developing an optimization model. Energy production and coal consumption at Indonesia Power and Nusantara Power operators are processed into specific coal consumption (specific fuel consumption/SFC). Indonesia Power's SFC is 613.70 tons/GWh and Nusantara Power's is 571.54 tons/GWh. The model uses linear programming with decision variables for energy allocation E1 and E2, an objective function to minimize Z, energy fulfillment constraints, and capacity limits. This study uses comparisons with D+5% and D+10% scenarios to see if there are any changes in energy use.. The results show that the optimization prioritizes Nusantara Power with energy production optimization at a demand of 7000 GWh with coal consumption of 41752584 tons. The optimization of the allocation of Indonesia Power operators is 41,384.82 GWh and Nusantara Power is 28,615.18. This model can be used as an initial tool for coal-fired power plants to optimize fuel efficiency and analyze operator scenarios. In addition, this model can help operators prioritize units with low SFC at normal loads.